The Archbishopric of Manila Meets the Challenge of Shepherding Its Laity to Spiritual Maturity (1953-1963) - Melanie J. Magpantay; Antonio C. Hila (Philippine Social Science Journal, 2020)
This study discusses, narrates, and analyzes how Archbishop Rufino Santos continued the work started by the country’s first native Archbishop of Manila, Gabriel M. Reyes, in steering the archbishopric to attain its full spiritual maturity. The research used the historical method guided by Arnold Toynbee’s Challenge and Response Theory identifying the Archbishop of Manila as the “creative personality” whose responses to the challenges of the post-war Archdiocese of Manila formed a “creative minority” who helped him respond to the challenges during his stewardship. As the "creative personality," Archbishop Santos led a series of responses that began to stir the social awakening of the Catholic Church in the Philippines to make it responsive to the social issues affecting the Filipinos. These responses allowed Archbishop Santos to elevate the Catholic Action movement to include socio-political concerns, thereby awakening the laity's socio-political consciousness and linking this to their Filipino Catholic identity.